2015
DOI: 10.1074/mcp.m114.047571
|View full text |Cite
|
Sign up to set email alerts
|

Immunocapture-Selected Reaction Monitoring Screening Facilitates the Development of ELISA for the Measurement of Native TEX101 in Biological Fluids*

Abstract: Monoclonal antibodies that bind the native conformation of proteins are indispensable reagents for the development of immunoassays, production of therapeutic antibodies and delineating protein interaction networks by affinity purification-mass spectrometry. Antibodies generated against short peptides, protein fragments, or even full length recombinant proteins may not bind the native protein form in biological fluids, thus limiting their utility. Here, we report the application of immunocapture coupled with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 38 publications
(36 reference statements)
2
57
0
Order By: Relevance
“…We developed a first-of-a-kind TEX101 ELISA (35) and demonstrated its clinical utility in large cohorts of fertile, sub-fertile and infertile individuals (28). Since interactions between testis-specific proteins are particularly important, in the present study we first focused on elucidation of the human TEX101 interactome in testicular tissues, spermatozoa and SP.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We developed a first-of-a-kind TEX101 ELISA (35) and demonstrated its clinical utility in large cohorts of fertile, sub-fertile and infertile individuals (28). Since interactions between testis-specific proteins are particularly important, in the present study we first focused on elucidation of the human TEX101 interactome in testicular tissues, spermatozoa and SP.…”
Section: Discussionmentioning
confidence: 99%
“…1B), and were subsequently expanded in serum-free media and purified using protein G columns. We showed previously that the commercial polyclonal antibody ab69522 could capture native TEX101 (28,35). Immunocapture-SRM results revealed that our monoclonal anti-TEX101 antibodies possessed higher affinity for native TEX101 than ab69522 (Fig.…”
Section: Production Of Tex101 Protein and Mouse Monoclonal Antibodiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Since prostatic proteins are more concentrated in semen than in serum or urine, PCa biomarkers might be more easily identified and quantified in SP by mass spectrometry. We previously discovered male infertility biomarkers in SP and developed a simple 2-biomarker algorithm for the differential diagnosis of male infertility 23,24,58 . Our success with male infertility biomarkers motivated us to search for prostate cancer biomarkers in SP.…”
Section: Discussionmentioning
confidence: 99%